2014
DOI: 10.1182/blood-2013-10-532085
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial DNA copy number and future risk of B-cell lymphoma in a nested case-control study in the prospective EPIC cohort

Abstract: Key Points• This study strengthens the previous observation of elevated mitochondrial DNA copy number and future risk of chronic lymphocytic leukemia.It has been suggested that mitochondrial dysfunction and DNA damage are involved in lymphomagenesis. Increased copy number of mitochondrial DNA (mtDNA) as a compensatory mechanism of mitochondrial dysfunction previously has been associated with B-cell lymphomas, in particular chronic lymphocytic leukemia (CLL). However, current evidence is limited and based on a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 25 publications
2
38
0
Order By: Relevance
“…For example, in a recent report from Zhang et al, levels of mtDNA copy number were significantly higher in glioma tumor tissues ( n = 124) than non‐neoplastic brain tissues ( n = 27) . Our results are also consistent with reports from other cancer sites, including melanoma, lung cancer, renal cell carcinoma, breast cancer, chronic lymphocytic leukemia, non‐Hodgkin lymphoma, colorectal cancer, and pancreatic cancer . More intriguingly, the positive association is not only observed in case control studies, but also in nested case control studies .…”
Section: Discussionsupporting
confidence: 91%
“…For example, in a recent report from Zhang et al, levels of mtDNA copy number were significantly higher in glioma tumor tissues ( n = 124) than non‐neoplastic brain tissues ( n = 27) . Our results are also consistent with reports from other cancer sites, including melanoma, lung cancer, renal cell carcinoma, breast cancer, chronic lymphocytic leukemia, non‐Hodgkin lymphoma, colorectal cancer, and pancreatic cancer . More intriguingly, the positive association is not only observed in case control studies, but also in nested case control studies .…”
Section: Discussionsupporting
confidence: 91%
“…In our study, we found that mitochondrial DNA (mtDNA) copy number was higher in lymphoma cells carrying an acquired TERTp mutation, suggesting that TERT overexpression modulates mtDNA regulation. The exact mechanism through which altered mtDNA may contribute to lymphomagenesis still remains unclear; however, mitochondrial biogenesis is a biologic pathway to be considered [34].…”
Section: Discussionmentioning
confidence: 99%
“…Although chemotherapy was shown to induce heterotrophic mtDNA mutations in CLL [29], Meierhofer et al found that blood transfusions might have ‘contaminated’ the tested samples with donors’ blood cell mitochondria [30] harboring abnormalities in hot spots that are frequently mutated in the general population [31]. Nevertheless, although the mtDNA structure of patients with CLL is no different from that of normal individuals, several studies showed that an increase in mtDNA copy numbers is associated with an increased risk for the development of CLL and non-Hodgkin’s Lymphoma [32,33]. …”
Section: Oxidative Phosphorylation In Cllmentioning
confidence: 99%